Antioxidant Capacity and Phytochemical Profile of Jatropha curcas L. Leaf Extracts and Fractions Using the FRAP Method - Sadik, Fahmi; Nur, Amran; S. Somadayo, Nur Asma; Hartina, Sitti (Universitas Ahmad Dahlan, 2025)
This study explored the free radical scavenging potential of Jatropha curcas L. leaves, focusing on identifying active biochemical constituents and evaluating antioxidant efficacy through a series of extraction and chemical analysis procedures. Phytochemical screening confirmed the presence of several bioactive secondary metabolites, including alkaloids, saponins, triterpenoids, tannins, and flavonoids. In the Ferric Reducing Antioxidant Power (FRAP) assay, the ethyl-acetate fraction exhibited the highest level of antioxidant activity (9.19 ± 0.38 µmol TE/g), significantly higher than that of the ethanol extract (3.52 ± 0.71 µmol TE/g), as well as the aqueous and n-hexane fractions. This value corresponds to strong activity according to the TEAC classification, indicating that Jatropha curcas leaves are a promising source of natural antioxidants. The total phenolic content (TPC) was determined to be 6.78 ± 0.27% GAE, while the total flavonoid content (TFC) measured 1.35 ± 0.07% QE. These findings indicate that phenolic and flavonoid constituents play a primary role in the antioxidant activity of the extract. Variations significantly influenced the observed outcomes in the extraction methodology and solvent polarity. In summary, Jatropha curcas leaves possess substantial antioxidant potential, particularly within the ethyl-acetate fraction, supporting further development for nutraceutical and pharmaceutical applications.